Ground water quality of several wells in Jasin Melaka - Mohd. Talib Hj. Latif,; Zulfahmi Ali Rahman,; Jasni Yaakob,; Nurbaiza Baharudin,; Nur Azeany Arifin,; Ruzaidah Yusof ,; Ramlan Omar, (Universiti Kebangsaan Malaysia, 2003)
A study of ground water from several wells was carried out in Jasin, Melaka to determine its suitability for drinking and domestic used. Four times sampling trips (n=4) had been done between June and October, 2000. Water parameters determined were temperature, pH, conductivity, color, turbidity, total suspended solids (TSS), dissolved oxygen (DO), chemical oxygen demand (COD), biological oxygen demand (BOD), oil and grease (O&G), total dissolved solids (TDS), nutrients and heavy metals (Cd, Cu, Pb, Mn and Fe). All selected methodology selected used were recommended by APHA (1995). The study indicated that the concentration of all parameters chosen were below the maximum values recommended by Malaysian Department of Health for drinking water quality except for certain heavy metals. Water Quality Index (WQI) calculated showed that the quality of water for many of the wells was of in Class III and not suitable for drinking before any extensive treatment.